(untitled) (Revista de Crítica Literaria Latinoamericana, 2011)
This article proposes the hypothesis that the film El Chacal de Nahueltoro by Miguel Littín, together with the novel Eloy by Carlos Droguett, works as a hinge between former works (both literary and filmic) whose protagonist is a criminal, and other, more modern and known works such as Criminal by Jaime Pinos and Tony Manero by Pablo Larraín. The author argues that the presence of a criminal tradition in literature and film in Chile, with bandits and murderers, shows a way of agreement (via Hobsbawm and Foucault) between this individual and the law, regulation, the system, and the State.